Cryopreservation and freezability of epididymal and ejaculated stallion spermatozoa - TALLURI, TR; JHAMB, DINESH; PAUL, NILENDU; MEHTA, S C; SINGH, JITENDAR; DEDAR, R K; LEGHA, R A; PAL, YASH (The Indian Journal of Animal Sciences, 2023)
The aim of the present study was to compare the seminal attributes and freezability of the epididymal sperm recovered from castrated stallions and ejaculated semen collected through artificial vagina from the same stallions previously. The seminal quality parameters viz., viability, sperm morphology, plasma membrane functional integrity, acrosome integrity and mitochondrial membrane potential were studied, and recorded immediately after fresh semen collection/retrieval, before freezing, and after cryopreservation. Similar protocols were followed for freezing the epididymal and ejaculated semen. From the current study, it was observed that the sperm concentration of the epididymal recovered was significantly higher than that of fresh ejaculation. Other seminal parameters in thefresh sample, like total and progressive sperm motility, sperm membrane functional integrity, acrosome integrity and kinematic parameters like VSL, STR, and linearity were similar without any significant differences between both. However, mitochondrial membrane potential, BCF and linearity of the spermatozoa differed significantly between the groups after cryopreservation. From the current study, it can be concluded that the protocols used for cryopreserving the fresh ejaculates can be adopted for freezing the stallion epididymal spermatozoa without causing significant damage and through this method; elite stallion germplasm can be safely cryopreserved and conserved.